Povidon-iodine (betadine) in modern obstetric-gynecological practice - О. М. Носенко; Т. Я. Москаленко; А. В. Рутинская (Publishing House TRILIST, 2018)
The article describes the pharmacocodynamics of povidone-iodine, the release form under the brand name Betadine, pharmacological benefits, as well as evidence of its effectiveness in preventing infection in the field of surgical intervention. Povidone-iodine is indicated to be a depot of iodine, constantly releasing elemental iodine, which has strong oxidizing properties, and therefore most microorganisms are destroyed in vitro in less than a minute, and the main destructive effect of the drug occurs in the first 15-30 seconds. Povidone-iodine has a wide spectrum of antimicrobial and antiviral action. The data on medications of povidone-iodine in the form of vaginal suppositories, antiseptic solution and ointment under the trade name Betadine are presented. Own data on the effective use of vaginal suppositories in symptomatic vaginal dysbiosis caused by mixed opportunistic bacterial flora (facultative and obligate anaerobes) with the presence of Atopobium vaginae in diagnostically significant amounts are presented. In the presented comparative studies, the advantages of Betadine compared with other antiseptics in the spectrum of microbiological effects, resistance of microorganisms, effects on wound healing, dependence of the effect on the physico-chemical parameters of the environment, side effects, the purpose of application - prevention and/or treatment are shown. The results of recent comparative studies on the treatment of the surgical area with chlohexidine-alcohol and povidone-iodine, according to which povidone-iodine should still be considered acceptable for the preoperative treatment of the caesarean section, are highlighted. It is indicated that the irrigation of the wound cavity with an aqueous solution of povidone-iodine during surgery and before suturing the surgical wound is one of the WHO recommendations for the prevention of infection in the field of surgical intervention. The authors conclude that povidone-iodine, including Betadine, has a broad spectrum of antimicrobial and antiviral activity; high activity in the presence of organic compounds (blood, pus); ability to penetrate through biofilms, necrotic tissue, eschar; low incidence of antiseptic resistance; positive dynamics of wound healing by preventing the spread of inflammation and increasing the ability to heal; well tolerated by patients; low cost; ease of use.